Individual heterogeneity and airborne infection: Effect of non-uniform air distribution. (December 2022) - Jia, Wei; Cheng, Pan; Ma, Luping; Wang, Shengqi; Qian, Hua; Li, Yuguo
Abstract: The classical Wells–Riley equation assumes homogeneity of susceptible individuals and environments to airborne exposure. However, individual susceptibility to infection is mostly heterogeneous, and exposure variability could arise from differences in inhalation rate, spatiotemporal non-uniformity of infectious aerosol concentrations, and the exposure trajectory and time. Non-uniform air distribution results in spatial non-uniformity of infectious aerosol concentrations. The non-uniformity effect is essentially a problem of individual infection probability. Here, we derived a general dose-response equation and a heterogeneous Wells–Riley equation accounting for individual variability in infection probability. The heterogeneous Wells-Riley equation shows the potential of the zone air distribution effectiveness to consider spatial non-uniformity under steady-state conditions. An existing quanta generation rate formula was theoretically justified. The new equation was then applied to a restaurant reporting an outbreak of coronavirus disease 2019, with spatial and/or temporal heterogeneity of infectious aerosol concentrations. Our results show the need to include spatial non-uniformity in outbreak investigations. A hypothetical two-zone setup was used to demonstrate how the inter-zonal distribution of clean air and the inter-zonal exchange flow affect airborne infections. An infector in a poorly diluted zone with the greatest number of susceptible individuals would result in the most secondary infections, whereas an infector in a well-ventilated zone with few susceptible individuals would result in the least secondary infections. Graphical abstract: Image 1 Highlights: The individual inhalation probability of a virion in space was estimated. A new Wells–Riley equation was developed to determine individual infection probability. Spatial non-uniformity of clean air was found to significantly affect airborne infections. The zone air distribution effectiveness in the ASHRAE standard was linked to airborne infection risk. Outbreak investigations should consider airflow non-uniformity.